Co-occurrence of a reef-building coral and canopy-forming macroalgae in the Mediterranean Sea - PONS-FITA, ALÈSSIA; KERSTING, DIEGO K.; BALLESTEROS, ENRIC (Mediterranean Marine Science, 2021)
Canopy-forming macroalgae are amongst the main competitors of corals by affecting coral recruitment, growth of recruits and adults, fecundity and in the worst-case scenario causing coral bleaching and necrosis. However, potentially reef-building coral Cladocora caespitosa (Linnaeus, 1767) and canopy-forming macroalgae of the order Fucales (Cystoseira sensu lato) are known to concur in a few places of the Mediterranean Sea. Here we look at the small-scale relationships between Cladocora abundance and Cystoseira s. l. densities at three different places where they coexist. Relationships have turned out to be both species and site-specific even though most relationships are neutral, pointing to a predominant concurrence of corals and macroalgae at the small scale. These findings shed new information on the relationship between corals and fleshy macroalgae in a temperate environment and serve as a starting point for future studies addressing the interactions between C. caespitosa and Cystoseira s. l.